Characterization of DNA binding and pairing activities associated with the native SFPQ•NONO DNA repair protein complex - Udayakumar, Durga (Biochem Biophys Res Commun, 2015)
Nonhomologous end joining (NHEJ) is a major pathway for repair of DNA double-strand breaks. We have previously shown that a complex of SFPQ (PSF) and NONO (p54(nrb)) cooperates with Ku protein at an early step of NHEJ, forming a committed preligation complex and stimulating end-joining activity by 10-fold or more. SFPQ and NONO show no resemblance to other repair factors, and their mechanism of action is uncertain. Here, we use an optimized microwell-based assay to characterize the in vitro DNA binding behavior of the native SFPQ•NONO complex purified from human (HeLa) cells. SFPQ•NONO and Ku protein bind independently to DNA, with little evidence of cooperativity and only slight mutual interference at high concentration. Whereas Ku protein requires free DNA ends for binding, SFPQ•NONO does not. Both Ku and SFPQ•NONO have pairing activity, as measured by the ability of DNA-bound protein to capture a second DNA fragment in a microwell-based assay. Additionally, SFPQ•NONO stimulates DNA-dependent protein kinase autophosphorylation, consistent with the ability to promote formation of a synaptic complex formation without occluding the DNA termini proper. These findings suggest that SFPQ•NONO promotes end joining by binding to internal DNA sequences and cooperating with other repair proteins to stabilize a synaptic pre-ligation complex.